Digital methods and tools to support healthy ageing - Ray, Pradeep; Liaw, Siaw-Teng; Serrano, Artur (Institution of Engineering & Technology, 2021)
This book presents a discussion of evolving digital technologies, such as smart phones, assisted living, and innovative digitally based services that are helping to deliver quality, cost-effective and widely accessible healthcare for the elderly.
Keywords: Older people -- Care -- Technological innovations.; elektronické knihy; electronic books